(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
World energy consumption has increased dramatically in the last three decades of the last century. The increase in the cost of electricity goes up in parallel with the increase in the cost of world fuel. Educational institutions such as polytechnics are no exception to the effects of this increase. This paper discusses the development of an energy monitoring system from equipment and to identify the equipment that contributes to energy wastage in the institution. Energy is recorded using a modified Wi-Fi power socket that is integrated with the Home Assistant platform. Some equipment in the academic building was selected in this experiment. The developed system is able to control ON and OFF of the equipment and can also record the power, voltage and current values for all the equipment used. Based on observations, it was found that the amount of energy wasted for each equipment was 3.88 Kw (water filter), 0.4 Kw (Voltage regulator) and 0.1 Kw (photostat machine). The use of a comprehensive system has been able to help monitor the energy consumption of each equipment and indirectly reduce the cost of the institution's electricity bill.